Expression of survivin, CD117, and C-4:41 AM 5/16/2006erbB-2 in neuroendocrine carcinoma of the uterine cervix - Sukpan K. (2014)
Objective: To evaluate the expression and prognostic significance of survivin, CD117, and C-erbB-2 in neuroendocrine carcinoma of the uterine cervix. Materials and Methods: Immunohistochemical stains of survivin, CD117, and C-erbB-2 were evaluated in 100 cases of cervical neuroendocrine carcinoma. The findings were correlated with clinicopathologic variables and disease-free survival. Results: Expressions of survivin, CD117, and C-erbB-2 were detected in 27.0%, 12.0%, and 2.0% of the cases, respectively. Survivin-positive patients had a significantly younger mean age than the survivin-negative group (P = 0.033). In early-stage cases, tumor recurrence was significantly associated with lymph node metastasis (P = 0.005), depth of invasion (P = 0.028), and the presence of lymphovascular space invasion (P = 0.031) but not with the expression of survivin or CD117. Subgroup analysis in early-stage cases without lymph node metastasis (n = 32) showed that only survivin expression had a significant association with decreased disease-free survival (P = 0.041). Conclusions: Survivin expression may be a prognostic indicator for survival in early-stage neuroendocrine carcinoma of the uterine cervix without lymph node metastasis. Adjuvant survivin-targeted therapy may have potential benefit in patients with this tumor. Copyright © 2011 by IGCS and ESGO.